1992
DOI: 10.1002/path.1711680303
|View full text |Cite
|
Sign up to set email alerts
|

Tumour angiogenesis in prostatic carcinoma with and without bone marrow metastasis: A morphometric study

Abstract: One hundred and one cases of clinical prostatic carcinoma (PCa), primary site, were analysed to define the interrelationship between tumour angiogenesis, histological grade, and bone marrow metastasis. Tumour angiogenesis was determined by the blood capillary density ratio (BCDR; a/b), defined as the ratio between the area of the blood capillaries (a) and the area of the tumour (b). The BCDR was evaluated by a colour image analysis system employing a computerized morphometrical method. A total of 43 cases of P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
87
1
5

Year Published

1994
1994
1998
1998

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 225 publications
(95 citation statements)
references
References 19 publications
2
87
1
5
Order By: Relevance
“…14,28 Also MVC has been shown to be a predictor of metastasis of prostate cancer to lymph nodes 11,16 and bone marrow. 15 One recent study reported that the center of the neoplasm had higher angiogenic activity than adjacent benign tissue or the periphery of the tumour. 29 It has been suggested that other endothelial markers such as CD31 and CD34 are more sensitive than FVIII to identify microvessels.…”
Section: Discussionmentioning
confidence: 99%
“…14,28 Also MVC has been shown to be a predictor of metastasis of prostate cancer to lymph nodes 11,16 and bone marrow. 15 One recent study reported that the center of the neoplasm had higher angiogenic activity than adjacent benign tissue or the periphery of the tumour. 29 It has been suggested that other endothelial markers such as CD31 and CD34 are more sensitive than FVIII to identify microvessels.…”
Section: Discussionmentioning
confidence: 99%
“…Increased MVD has been correlated with a higher incidence of metastasis and a worse prognosis in both breast (Weidner et al, 1992;Horak et al, 1992) and prostatic carcinoma (Vesalainen et al, 1994;Wakui et al, 1992). Two studies in prostate cancer, one in invasive carcinoma (Weidner et al, 1993) and the other in clinically localised disease (Hall et al, 1994), concluded that MVD had prognostic potential.…”
Section: Immunocytochemical Analysismentioning
confidence: 99%
“…These samples were insufficient to count vessels in hot spots, a procedure regarded as essential for determining the angiogenic potential of tumors according to Weidner (1995). However, in other studies too, MVD was not assessed in hot spots, yet a correlation of MVD with the occurrence of metastases was found (Wakui et al, 1992;Brawer et al, 1994). Moreover, in our study this restriction applied both to UPT and to known primary patients.…”
Section: Survival Analysis In Upt Patientsmentioning
confidence: 77%